Los clanes del narcotráfico en el campo de Gibraltar - Oliver, Francesc Xavier Moreno (Quadernos de criminología, 2021)
Morocco is the world's largest producer and exporter of hashish for recreational purposes. For the smuggling of the cited drug, the different organized crime groups and criminal gangs (BACRIM) specialized in this type of trafficking use varied logistical resources and routes, one of the main destinations is the Campo de Gibraltar in Cádiz.